If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + -5(p + -1q) + -1p = 0 7p + (p * -5 + -1q * -5) + -1p = 0 7p + (-5p + 5q) + -1p = 0 Reorder the terms: 7p + -5p + -1p + 5q = 0 Combine like terms: 7p + -5p = 2p 2p + -1p + 5q = 0 Combine like terms: 2p + -1p = 1p 1p + 5q = 0 Solving 1p + 5q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5q' to each side of the equation. 1p + 5q + -5q = 0 + -5q Combine like terms: 5q + -5q = 0 1p + 0 = 0 + -5q 1p = 0 + -5q Remove the zero: 1p = -5q Divide each side by '1'. p = -5q Simplifying p = -5q
| -2/3*4= | | log(8x+11)=2 | | 2x+3=3x+20 | | 7x+2(x-5)=4 | | 5X+6+4X=3-6 | | 10(x+2)-4(2x+1)=2(x+6) | | E^9x=5.9 | | F(x)=-x^2+8x+7 | | 9n+2n-5=-60 | | 8(a+2)=72 | | F(x)=-x^2-6x+5 | | 3x-4+5x+20=180 | | 3x-4+5x+20=360 | | 5=log(x+1) | | 8+5(x-7)=8-4(x-8) | | 5X-7X+X=4-2X | | 5e+2.5=2.5-7.5c | | -5.5+3.5(1-9.5k)=25.5 | | 0.24x+3.8x=-2.02 | | 8+5x-35x=8-4x-32 | | 4(2b-3x)=7b+5x | | 8+5x-35x=8-4x+32 | | 8x-17b=7x | | n=2/4*7/8 | | 7+3x=-5x+13 | | 12x-(x+3)=30 | | 4(2x-3b)=7x+5b | | 12x-(x+3)=4 | | 2x-3+4x+1=0 | | l-100=253 | | 9y-9=6y+6 | | 18x^2+3-53x=0 |